2008
DOI: 10.1111/j.1600-0706.2008.17225.x
|View full text |Cite
|
Sign up to set email alerts
|

Who are we sampling? Apparent survival differs between methods in a secretive species

Abstract: Survival is a fundamental parameter in population dynamics with increasing importance in the management and conservation strategies of wildlife populations. Survival probability in vertebrates is usually estimated by live-encounter data obtained by means of physical markÁcaptureÁrecapture protocols. Non-invasive acoustic marking relying on individual-specific features of signals has been alternatively applied as a marking technique, especially in secretive species. Nevertheless, to date no research has compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 37 publications
3
48
0
Order By: Relevance
“…All fragments of a suitable habitat separated by a distance of less than 1 km from the nearest neighbour fragment were assigned to the same population (figure 1), based on spatial analyses of connectivity and the species' behaviour [18]. Dupont's lark population sizes were calculated as the number of occupied territories through territory mapping of males aided by its acoustic identification and observations of individually colour-banded birds [17]. Dupont's lark breeding densities were determined as (i) the number of occupied territories divided by patch size, and (ii) the mean distance between the nearest singing male neighbours [16,18].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All fragments of a suitable habitat separated by a distance of less than 1 km from the nearest neighbour fragment were assigned to the same population (figure 1), based on spatial analyses of connectivity and the species' behaviour [18]. Dupont's lark population sizes were calculated as the number of occupied territories through territory mapping of males aided by its acoustic identification and observations of individually colour-banded birds [17]. Dupont's lark breeding densities were determined as (i) the number of occupied territories divided by patch size, and (ii) the mean distance between the nearest singing male neighbours [16,18].…”
Section: Methodsmentioning
confidence: 99%
“…Remarkably, our results resemble those obtained by Lindström et al [33], which showed a consistent increase in three parasites (two species of feather mites and avian pox virus) in island populations of Darwin's finches with increasing island size. Our host study model species has a very low dispersal rate [16,17], as well as disrupted culture transmission at small spatial scales [34]. All of these factors suggest an unusual scenario of island effects in a mainland vertebrate.…”
Section: R E T R a C T E Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Dupont's lark is currently the subject of several conservation research studies (Garza et al, 2005;Laiolo and Tella, 2005, 2006a,b, 2007Seoane et al, 2006;Suárez et al, 2009;Vögeli et al, 2008Vögeli et al, , 2010Vögeli et al, , 2011a, genetic processes occurring within and among populations remain largely unknown. A recent phylogenetic study showed that the Spanish populations are isolated from the Moroccan ones (García et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it should be stressed that bird local populations are rarely isolated, and natal and breeding dispersal permits females to move and come into contact with different social environments [64]. Lark females dispersing in winter or early spring [65,66], for instance, may experience the songs of males from different local neighbourhoods and eventually choose their breeding territories on the basis of song cues at the transect or site scale [67,68].…”
Section: Discussionmentioning
confidence: 99%